Monetary or nonmonetary compensation for service failure? A study of customer preferences under various loci of causality. (April 2015) - Fu, Hui; Wu, Doris Chenguang; Huang, Songshan (Sam); Song, Haiyan; Gong, Jinhong
Abstract: When service failures occur, hotels adopt various strategies to compensate guests in order to maintain their satisfaction. This study examines the effectiveness of different post-failure compensation strategies in scenarios presenting various loci of causality. The results indicate that across all scenarios, strategies combining monetary and nonmonetary compensation result in higher customer satisfaction than those which offer one or the other. In addition, nonmonetary compensation results in higher satisfaction than monetary redress when the service failure has been caused by the hotel. The study also identified a partial mediation of the interaction effect of service failure causality and compensation type on customer satisfaction by three kinds of justice.